Management of Orofacial Herpes (Visarpa) Through Ayurvedic Approach (International Journal of Ayurveda and Pharma Research, 2023)
Herpes Simplex infection of mouth and face is known as ‘Oro Facial Herpes Simplex (cold sores). The incident rate of herpes viral infection is found to be around 7-14% in adolescents in India. It is caused by herpes simplex virus type 1 (HSVL). Oro facial herpes simplex causes inflamed and localized blisters that pop, weep and form crusts. At initial stage it shows symptoms like redness, swelling, heat and itching along with pain. Over a period of time the blisters leak out and become sores. According to Ayurveda literature, this disease can be co-related with ‘Pittaja Visarpa.’ Here presenting a case report of 52-year-old male with sudden onset of painful blisters, redness and burning pain on the jaw region. The patient was managed with Sutshekhar rasa, Avipattikar churna as oral medication and Jatyadi oil (Sheath Veda) and Khas Anantmool Ayurvedic cream (Sheath Veda) for local application over the jaw region. The patient showed improvement within two weeks and got significant relief over a month.